2022
DOI: 10.1002/bin.1856
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for automatically reinforced vocal stereotypy for individuals with autism spectrum disorder: A literature and meta‐analytic review

Abstract: Individuals with Autism Spectrum Disorder may engage in repetitive vocal behaviors which interfere with a structured environment and social inclusion. If untreated, these vocal behaviors maintain into adulthood potentially impeding gainful employment and independent living. This analysis specifically focused on treatments available for presumed or functionally determined automatically reinforced repetitive vocal behaviors, also known as vocal stereotypy. For this review, a systematic keyword search of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…As discussed earlier, for individuals engaging in stereotypy, an extended no‐interaction screening as described by Querim et al (2013) should be considered before manipulating other environmental variables. For a detailed description of successful treatment recommendations following assessment for these individuals, see Mantzoros et al (2022; vocal stereotypy) or Akers et al (2020; motor stereotypy). Similar results were obtained for individuals engaging in pica, for which 12 of 16 (75.0%) outcomes showed maintenance by automatic reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, for individuals engaging in stereotypy, an extended no‐interaction screening as described by Querim et al (2013) should be considered before manipulating other environmental variables. For a detailed description of successful treatment recommendations following assessment for these individuals, see Mantzoros et al (2022; vocal stereotypy) or Akers et al (2020; motor stereotypy). Similar results were obtained for individuals engaging in pica, for which 12 of 16 (75.0%) outcomes showed maintenance by automatic reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous reviews (Mantzoros et al, 2022;Martinez & Betz, 2013;Ryan et al, 2022), the current review found limited reports of social validity data. Given behaviors maintained by automatic reinforcement are often selected based on the acceptability of those behaviors in the individual's given environment, it may behoove researchers and clinicians alike to collect social validity data on the goals and procedures across settings where the behavior occurs and intervene only where warranted.…”
Section: Discussionmentioning
confidence: 86%
“…Through their analyses, Dowdy et al provided quantitative support that RIRD produces robust effect sizes. Mantzoros et al (2022) reviewed the literature for vocal stereotypy and emphasized the efficacy of RIRD as a solitary procedure. Most recently, Ryan et al (2022) conducted a review of RIRD applications between 2007 and 2021 that included categories for several important considerations, such as inclusion of maintenance data and social validity measures.…”
mentioning
confidence: 99%
“…It is important to consider that a behavior such as VS may not require an individual to reach zero‐levels of behavior and/or may only require a reduction in environments where the behavior interferes with participation, performance, or skill acquisition (Mantzoros et al., 2022). As this is seemingly a preferred behavior for the individual, ethically it is ideal to target the behavior only under circumstances where rates of engagement are detrimental to the individual's meaningful engagement with others and independent living skills.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention literature on VS has grown rapidly during the last two decades and includes interventions such as response interruption and redirection (e.g., Ahearn et al., 2007), matched stimulation (e.g., Groskreutz et al., 2011), differential reinforcement procedures (e.g., Taylor et al., 2005), and punishment procedures (e.g., Falcomata et al., 2004) among others. Reviews have documented the effects of these interventions on reducing VS (Lanovaz & Sladeczek, 2012; Mantzoros et al., 2022); however, there are important considerations for implementing in applied settings as each intervention has benefits and challenges to consider. For instance, reinforcement‐based strategies provide alternative reinforcement that competes with the VS; however, treatment effects may dissipate when the schedule of reinforcement is thinned to a level that no longer competes favorably with the rate of reinforcement obtained via VS (Ahrens et al., 2011).…”
Section: Introductionmentioning
confidence: 99%